Broadcasting Policy in Canada, Second Edition. - Armstrong, Robert, 1946- (University of Toronto Press, 2016)
The second edition of Broadcasting Policy in Canada offers a comprehensive overview of the policies that provide the foundation for the Canadian broadcasting system, including discussion of topics such as Canadian content, media regulation, and program financing.